Monodispersity and stability of Gold nanoparticles stabilized by using polyvinyl alcohol - Pimpang P. (2014)
Gold nanoparticles (Au NPs) have been prepared by reduction of hydrogen tetrachloroaurate aqueous solution (HAuCl4) with trisodium citrate and stabilized with polyvinyl alcohol (PVA). The optimization of Au NPs was obtained by varying the volume of trisodium citrate from 0.4 - 0.8 mL, and characterized by UV-vis spectroscopy and transmission electron microscopy (TEM). It was found that the absorbance spectra exhibited its absorption peak at around 520 nm for all cases, with a minimum value at 0.7 mL of trisodium citrate. This suggested that the size of Au NPs to be smallest at condition 0.7 mL trisodium citrate, thereby indicating the optimum conditions. Stability of Au NPs was achieved by monitoring absorbance of Au NPs over regular time periods. It was found that wavelength at maximum absorbance changed with time after synthesis except for the 0.7 mL condition which was stable. This suggested that, at condition 0.7 mL, the Au NPs were quite stable up to 700 hours; this could be explored for further applications. Moreover, TEM results showed Au NPs obtained at optimum condition exhibited near spherical shapes with a mean diameter and standard deviation of 4.5 and 1.4 nm, respectively. Also moreover, FT-IR result suggested that Au NPs were coated with a PVA layer.